Phase segregation of metastable quenched liquid mixtures and the effect of the quenching rate. (4th March 2019) - Califano, Filomena; Mauri, Roberto
ABSTRACT: The effect of the quenching rate on the phase separation of partially miscible liquid mixtures is studied, showing that it may influence the growth rate of single-phase domains. In particular, the phase separation of metastable binary mixtures in the presence of strong emulsifiers appears to be heavily retarded. These effects constitute an important limitation to the phase transition extraction process introduced by the authors in previous works, which is based on the fact that phase separation of unstable mixtures is rapid, even in the presence of surface active compounds.